Risk-Based Application of Business Licensing at the One-Stop Investment and Integrated Service Office of Kotamobagu City - Mamonto, Aryanto; Thelma Wawointana; Laurens Bulo (Technium Social Sciences Journal, 2025)
The main purpose of this study is to describe and analyze the importance of online business investment activity reports through the Risk-Based Application of Business Licensing and to determine the impact of using the Risk-Based Application of Business Licensing at the Kotamobagu City One-Stop Investment and Integrated Services Office in submitting online business investment activity reports. The approach used in this research is a qualitative descriptive approach. The results showed that the Risk-Based Business Licensing Application is a system used by the Government of the Republic of Indonesia in this case the Ministry of Investment / Investment Coordinating Board of the Republic of Indonesia which aims to simplify and simplify the business licensing process. This system is known as the Online Single Submission Risk Based Approach which was introduced as part of licensing reform through the Job Creation Law (Law No. 11 of 2020). Business Licensing is now issued called the Business Identification Number or NIB, once issued it is used forever by business actors in carrying out their business activities. In the past, when taking care of business licensing, there was something called SITU (Business Place Permit), SIUP (Trade Business License), Hinderordonnantie (HO) or Nuisance Permit and TDP (Company Registration Certificate), all of these forms of business licenses have an expiration date and must be renewed every certain period of the year in accordance with the validity period. With the current business licensing system whose name is Business Identification Number (NIB), business actors no longer need to extend their business licenses because this business license is valid as long as business actors carry out their business activities, business actors are required to submit business activity developments, namely the Online Investment Activity Report (LKPM) through Online Single Submission of the Risk Based Aplication of Business Licensing (OSS-RBA). Investment Activity Report, hereinafter abbreviated as LKPM, is a report on the development of Investment realization and problems faced by Business Actors which must be made and submitted periodically. The purpose of LKPM Online Reporting is to monitor and evaluate the progress of investment realization carried out by the Company.